Three different Fourier‐transform mid‐infrared sampling techniques to characterize bio‐organic samples. Issue 5 (8th July 2020) - Bekiaris, Georgios; Peltre, Clément; Barsberg, Søren T.; Bruun, Sander; Sørensen, Klavs M.; Engelsen, Søren B.; Magid, Jakob; Hansen, Mette; Jensen, Lars S.
Abstract: In recent years, there has been a surge in the number of applications of Fourier‐transform mid‐infrared (FTIR) spectroscopy for the characterization of environmental samples and prediction of some of their properties whose measurement has traditionally involved time‐consuming and costly methods. However, there are several different mid‐infrared techniques available, and there is a gap in knowledge regarding the best‐suited technique for recording informative spectra of different types of environmental samples. This study compared the three most widespread FTIR techniques using solid and liquid samples. A total of 11 environmental samples belonging to four categories were analyzed with attenuated total reflectance (ATR), photoacoustic (PAS), and diffuse reflectance (DR) FTIR spectroscopy. Overall, PAS‐FTIR was the best technique, providing a greater amount of information, especially for opaque samples (i.e., organic waste, biochar, and soil), than ATR‐FTIR and DR‐FTIR spectroscopy. Attenuated total reflectance FTIR provided the best spectra for soft samples, such as plant materials, probably due to their ability to achieve good optical contact with the ATR crystal. Finally, DR‐FTIR performed relatively well for most samples but was found to be more sensitive to moisture in the samples, resulting in noise in specific areas, and was less sensitive in bond vibrations related to Si.